2021
DOI: 10.1111/faf.12590
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations for research on small‐scale fisheries and blue crimes

Abstract: Blue crimes-crimes at sea-are receiving growing academic and policy attention, yet research remains relatively sparse when considering the diversity and global scale of crimes, impacts and policy implications (Bueger & Edmunds, 2020;Isaacs & Witbooi, 2019;Song et al., 2020). There is a need to better understand the relations between small-scale fisheries (SSF), blue crimes and law enforcement Witbooi et al., 2020). SSF account for at least 90 per cent of the fish workers worldwide, playing a crucial role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Several studies have shown the detrimental effects of the IUU fishing discourse on SSF (e.g. Hauck, 2008; Saputra, 2020;Satizábal et al, 2021; Song et al, 2020). Firstly, its generalist sense disregards the diversity, legitimacy and sustainability of SSF and their governance systems.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the detrimental effects of the IUU fishing discourse on SSF (e.g. Hauck, 2008; Saputra, 2020;Satizábal et al, 2021; Song et al, 2020). Firstly, its generalist sense disregards the diversity, legitimacy and sustainability of SSF and their governance systems.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, small-scale fishers experience material, political, ecological, and social challenges (Barbesgaard, 2018;Bavinck et al, 2018) including organised crime (Witbooi et al, 2020), blue crime (Satizábal et al, 2021) such as criminal activities including sea-piracy, robbery, illegal fishing, dumping toxic materials, and drug trafficking in the sea. Displacement due to industrial 'extractivist' in the form of large-scale development in coasts (Acosta, 2013) and aquaculture expansion (Adduci 2009;Bogadóttir 2020), blue growth threats (Barbesgaard 2018;Bennett et al, 2021) cause fisheries injustice (Mills, 2018), recently, termed as epistemic injusticetestimonial and hermeneutical (Schreiber et al, 2022).…”
Section: Ssf and Historical Trends Of Strugglementioning
confidence: 99%
“…Illegal fishing refers to fishing activities that violate existing laws, such as fishing in foreign waters without permission and activities that do not abide by regulations of the Regional Fisheries Management Organisations (RFMOs) that the state under which the vessel operates has to follow, or by other international or national legislation. Illegal fishing is often linked to other forms of 'fish crimes' (crimes related to the fishing sector, including labour abuses, document fraud, smuggling and money laundering, see Belhabib, Le Billon and Wrathall 2020;INTERPOL 2020), though we caution against framing all illegal fishing activities as organised crime (Satizábal et al 2021).…”
Section: Introductionmentioning
confidence: 99%